SHRI BABU JAGJIVAN RAM: A PIONEER OF DECOLONISATION MOVEMENT IN THE INDEPENDENT INDIA - Ranjan, Sanjiv; Shashi Kant; Pintu Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Babu Jagjivan Ram, a prominent Dalit leader and social reformer, was a pioneering force in India’s decolonization movement. Born in 1908 in a marginalized caste community, he overcame systemic discrimination and rose to become one of the most influential political figures in post-independence India. His journey from a humble background to a statesman symbolizes the resilience and determination of the oppressed classes in the fight for equality and social justice. Jagjivan Ram’s role in India’s freedom struggle was marked by his commitment to eradicating caste-based injustices while fighting for the country’s independence. As a member of the Indian National Congress, he played a crucial part in the Quit India Movement and led efforts to ensure that the voices of Dalits and other marginalized communities were included in the national discourse. He was also instrumental in forming the All-India Depressed Classes League, which advocated for the political and social rights of Dalits. After India gained independence in 1947, Jagjivan Ram continued to champion the cause of the downtrodden as a key member of independent India’s government. He held several important cabinet positions, including that of Defence Minister and Agriculture Minister. His contribution to the Green Revolution, which transformed India’s agricultural landscape, is particularly noteworthy. His leadership during the Indo-Pak war of 1971, which led to the creation of Bangladesh, further cemented his legacy as a visionary leader. Beyond politics, Jagjivan Ram’s life was a testament to the power of perseverance and the importance of inclusivity in nation-building. He dedicated his life to creating an India free of both colonial oppression and caste discrimination. His legacy continues to inspire movements for equality and justice in modern India.